Does metabolic syndrome influence short and long term durability of carotid endarterectomy and stenting? - Casana, R; Malloggi, C; Tolva, V; Odero, A; Bulbulia, R; Halliday, A; Silani, V (Wiley, 2018)
Aims: The metabolic syndrome (MetS) is composed of a cluster of related cardiovascular risk factors. The aim of the present study was to determine how MetS contributes to short‐ (30‐day) and long‐term complications and restenosis after carotid endarterectomy (CEA) or stenting (CAS). Methods: A consecutive cohort of 752 patients undergoing CEA (n = 314) and CAS (n = 438) in a single institution was examined, of which 296 (39.4%) were identified as having MetS. All patients were followed‐up with carotid duplex ultrasound scan of the supraaortic vessels and a neurological assessment of symptoms status at 30‐day postprocedure and at 3, 6, and 12 months, with annual follow‐up thereafter for 3 years. Results: Patients with MetS had a significant increased risk in their 30‐day death, major adverse events (MAE), and restenosis rates, both after CEA and after CAS (death: 0.7% vs 0.0%; MAE: 5.3% vs 2.7%; and restenosis: 1.7% vs 0.2%; p < 0.05). The MAE and restenosis rates remained statistically different at 36 months, with both procedures (29.2% vs 24.2% and 9.5% vs 3.3%, p < 0.05, for patients with and without MetS, respectively). Among the components of MetS, high fasting serum glucose, low high‐density lipoprotein cholesterol, and elevated body mass index were associated with increased risk of complications at 30 days and within 36 months. Conclusions: The current study suggested that the presence of MetS is an important risk factor for morbidity and restenosis after CEA and CAS.